2017
DOI: 10.2355/isijinternational.isijint-2016-569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO, Na<sub>2</sub>O, and B<sub>2</sub>O<sub>3</sub> on the Viscosity and Structure of Cr<sub>2</sub>O<sub>3</sub>-bearing CaO–SiO<sub>2</sub>–Al<sub>2</sub>O<sub>3</sub> Slags

Abstract: slags was greater than that of Na 2 O. This could be due to the different ways in which these additives modify the slag network structure. Raman spectroscopy analysis revealed that MgO and Na 2 O work as network modifiers, and the degree of polymerization (DOP) of slags increases with the addition of MgO and Na 2 O. MgO is more effective at modifying the structure than Na 2 O, because Na 2 O may be more likely to produce network former [AlO 4 ] units. In this study, Cr 2 O 3 and B 2 O 3 are found to behave as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The change in viscosity is not merely correlated to the slag components, but also combined with the structure in the melt . According to the studies by Wang and other researchers, the viscosity‐structure relationship is really essential for investigating slag properties in various slag systems. Therefore, the structure of slags No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in viscosity is not merely correlated to the slag components, but also combined with the structure in the melt . According to the studies by Wang and other researchers, the viscosity‐structure relationship is really essential for investigating slag properties in various slag systems. Therefore, the structure of slags No.…”
Section: Resultsmentioning
confidence: 99%
“…As proposed by Maehara and other researchers, Raman scattering efficiency of Si–O bond depends on the type of Q n species, however, it is difficult for the authors to determine the exact Q n distribution by another experimental technique nuclear magnetic resonance (NMR) to calibrate the Raman area fraction. Based on the studies by Li et al, the relative area fraction of individual unit can be used for quantitative estimation, and the concept of which is adopted in the present work. The relative area fraction of individual unit is obtained by dividing the integrated area of all the structural units.…”
Section: Resultsmentioning
confidence: 99%
“…2and 3that the viscosity of slag plays a dominant role in coarsening of crystals in slag. Li et al reported that B 2 O 3 addition leads to the formation of low melting point eutectics and weaker polymerization strength, which contribute to the decrease in slag viscosity [33]. Therefore, according to Eqs.…”
Section: Disintegration Behavior Of Slagsmentioning
confidence: 99%
“…Investigation indicated that B 2 O 3 show better fluxing actions on CaO-based slags, 6) and B 2 O 3 addition also led to the formation of low melting point eutectics. 8) Fig. 9.…”
Section: Crystallization Process Of the Mold Fluxesmentioning
confidence: 99%
“…B 2 O 3 addition also led to the formation of low melting point eutectics and weaker polymerization strength. 8) In present new-desigened slag system, B 2 O 3 was added not only to decrease the melting temperature, but also to improve the inclusion absorption ability of the slag. According to Wan,9) …”
Section: Introductionmentioning
confidence: 99%